2006
DOI: 10.1620/tjem.208.203
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Angioplasty-Related Inflammation by Pre-Procedural Treatment with Trimetazidine

Abstract: Percutaneous transluminal coronary angioplasty (PTCA) has been recognized as a reliable treatment procedure for acute reversible ischemia and reperfusion. Ischemic reperfusion cycle in PTCA leads to the systemic inflammation and extensive tissue injury by the production of reactive oxygen species including nitric oxide (NO) radicals. In patients with coronary artery disease, undergoing PTCA, the effects of trimetazidine (TMZ), a piperazine-derivative anti-anginal drug, were studied on several indirect markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 71 publications
3
26
0
1
Order By: Relevance
“…Medicaments that suppress inflammatory response to the damage, as recently described for trimetazidine (Kuralay et al 2006), could be of additional interest, while the use of aspirin known as an ti-in fl ammato r y d r u g th at h as anticoagulating and antioxidant features should be considered with care (Hobikoglu et al 2005). Therefore, novel bioengineered compounds should be tested as well as cocktails of classical antioxidants in order to reduce the reperfusion injury within the myocardium (Hung et al 2001), which may become efficient supportive treatments for myocardial recovery after AMI and successful convalescence of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Medicaments that suppress inflammatory response to the damage, as recently described for trimetazidine (Kuralay et al 2006), could be of additional interest, while the use of aspirin known as an ti-in fl ammato r y d r u g th at h as anticoagulating and antioxidant features should be considered with care (Hobikoglu et al 2005). Therefore, novel bioengineered compounds should be tested as well as cocktails of classical antioxidants in order to reduce the reperfusion injury within the myocardium (Hung et al 2001), which may become efficient supportive treatments for myocardial recovery after AMI and successful convalescence of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of trimetazidine can be attributed to decrease the levels of TNF α , NO products and CRP. [7][8][9][10] Though the results of the present study do not point at actual mechanism of trimetazidine on inflammation, this effect can be attributed to the effect of trimetazidine to decrease TNF α as reported in previous studies. [7][8][9][10] This study shows that in addition to anti anginal activity, trimetazidine may also possess anti-inflammatory properties that could be of additional benefit in the treatment of atherosclerosis and their complications like reinfarction and infarct extension, and also in preventing cardiovascular events like restenosis after PCI.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly certain studies have reported that metabolic modulator trimetazidine, which is an antianginal drug, inhibits the inflammatory markers like C reactive protein(CRP), nitric oxide products (nitrite and nitrates), interleukins (IL-1, IL-6) and TNF alpha. [7][8][9] But another study suggested that trimetazidine showed no significant reduction in the levels of IL-8, TNF-α, complement 3 and 5 and CRP. 10 Review of literature revealed paucity of studies regarding anti-inflammatory activity of the above mentioned drug in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al reported that TMZ protected against smokinginduced left ventricular remodeling via attenuating oxidative stress, apoptosis, and infl ammation (10) . Kuralay et al found that TMZ signifi cantly reduced CRP and TNF-α levels after coronary angioplasty (11) . Lipoprotein-associated phospholipase A 2 is a novel and unique biomarker, highly specifi c for vascular infl ammation and Hematocrit (%) 40.6 ± 3.5…”
Section: Discussionmentioning
confidence: 99%